2015
DOI: 10.1007/s10508-015-0564-7
|View full text |Cite
|
Sign up to set email alerts
|

Minor Physical Anomalies as a Window into the Prenatal Origins of Pedophilia

Abstract: Evidence is steadily accumulating to support a neurodevelopmental basis for pedophilia. This includes increased incidence of non-right-handedness, which is a result primarily of prenatal neural development and solidified very early in life. Minor physical anomalies (MPAs; superficial deviations from typical morphological development, such as un-detached earlobes) also develop only prenatally, suggesting them as another potential marker of atypical physiological development during the prenatal period among pedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
0
25
0
2
Order By: Relevance
“…Research supports the hypothesis of an association between MPAs and several neuropsychiatric disorders, such as autism and schizophrenia (31,32). Pedophilic individuals seem to exhibit a greater number of MPAs relative to samples of individuals with schizophrenia as well as healthy controls: Dyshniku and colleagues found that MPA indices were positively associated with multiple indicators of pedophilia, including phallometric responses to sexual stimuli, number of child but not adult victims, and possession of child sexual exploitation material (30). There is also a relationship between adult men's height and pre-and perinatal factors, such as genetic predisposition or conditions in utero (33).…”
Section: Minor Physical Anomalies and Congenital Malformationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Research supports the hypothesis of an association between MPAs and several neuropsychiatric disorders, such as autism and schizophrenia (31,32). Pedophilic individuals seem to exhibit a greater number of MPAs relative to samples of individuals with schizophrenia as well as healthy controls: Dyshniku and colleagues found that MPA indices were positively associated with multiple indicators of pedophilia, including phallometric responses to sexual stimuli, number of child but not adult victims, and possession of child sexual exploitation material (30). There is also a relationship between adult men's height and pre-and perinatal factors, such as genetic predisposition or conditions in utero (33).…”
Section: Minor Physical Anomalies and Congenital Malformationsmentioning
confidence: 80%
“…They are supposed to develop during the first and/or early second trimester of gestation (27)(28)(29). Even though the exact mechanism remains elusive, there are some indications that besides genetic factors, also environmental perturbations (e.g., hypoxic events) during early embryonic period may determine the extent and nature of malformations (27,30). Research supports the hypothesis of an association between MPAs and several neuropsychiatric disorders, such as autism and schizophrenia (31,32).…”
Section: Minor Physical Anomalies and Congenital Malformationsmentioning
confidence: 99%
“…The phallometric Pedophilia Index was more accurate in distinguishing pedophiles from teleiophiles than the Hebephilia Index was in distinguishing hebephiles from teleiophiles. Such a pattern would be expectable: Empirically, features and correlates of hebephilia frequently fall midway between those of pedophilia and teleiophilia [28], including in terms of IQ [29], handedness [18,[29][30][31], physical height [32], "minor physical anomalies" [33], and histories of school-grade failure or special education placement [34]. Moreover, because prepubescent children are more distinct from adults than are pubescent children, pedophilia would be expected to be more distinct from teleiophilia than is hebephilia, and therefore, easier to distinguish from teleiophilia.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, MPAs have been found to be higher in schizophrenics who murder compared to both schizophrenics who do not murder as well as to normal controls (Tenyi et al., ). Within offenders, MPAs have been associated with more signs of pedophilic tendencies (Dyshniku, Murray, Fazio, Lykins, & Cantor, ). Taken together, these studies have suggested that there are early neurodevelopmental processes under way in those who later in life manifest violence.…”
Section: Early Health Risk Factorsmentioning
confidence: 99%